Energetic renewal in large housing estates. - (:unkn) unknown (My University, 2010)
Angesichts des Klimawandels und stetig steigender Energiepreise sind zentrale politische Ziele der Bundesregierung, die Energieeffizienz und die Reduktion von Treibhausgasen voranzutreiben. Der Energiebedarf im Wohnungswesen macht 40 % des gesamtdeutschen Energiebedarfs aus. Von 39 Millionen Wohnhäusern wurden 75 % vor 1979 erbaut und besitzen eine unzureichende Energieeffizienz. Um Erneuerungsprozesse zu fördern und Eigentümer großer Wohnanlagen bei der Erfassung integrierter Konzepte zu unterstützen, hat das Bundesministerium für Verkehr, Bau und Stadtentwicklung im Januar 2009 zu dem Wettbewerb "Energetische Sanierung in großen Wohnanlagen basierend auf integrierten Konzepten für Stadtviertel" aufgerufen. Die Publikation zeigt wie dieser deutschlandweite Wettbewerb neue Impulse in der Wohnungswirtschaft gegeben hat.

Facing global challenges of climate change as well as augmenting energy prices, energy efficiency and decrease of the emission of greenhouse gases are central political aims of the Federal government of Germany. In order to foster on-going renewal processes and to support owners of large housing estates the Federal Ministry of Transport, Building and Urban Affairs invited to a competition Energetic renewal in large housing estates in 2009 which is the central topic of the paper. The competition aimed at housing associations, private owners or co-operations of different partners with a housing stock of 500 apartments at least. The participants had to show how they meet their actual challenges by managing energetic rehabilitation, neighbourhood improvement and social aspects in an economically reasonable way. The competition addressed to owners of large housing estates in order to initiate the energetic redevelopment of urban quarters as a whole. After an outline of the national context, the paper focuses on the aim and approach of the competition and highlights that the German-wide competition gave new impulses: For the first time, integrated concepts for the redevelopment of larger districts were drawn by private companies or associations, not any public authority. The paper presents an overview about the course of the competition and its participants and shows how the housing companies realised the integrated approach towards district development with focus on energy efficiency.
Keywords: Bebauung; Wohnungswesen; Wohnanlage; Energieverbrauch; Energetische Sanierung; Energieeffizienz